EXAMINING FINANCIAL READINESS FOR MARRIAGE: A DESCRIPTIVE STUDY OF YOUNG COUPLES IN RAUB DISTRICT - Muhamad, Muhammad Isma Irfan; Musa, Muhammad Fadhli; Ridzwan, Rikinorhakis (Journal of Islamic, Social, Economics and Development, 2024)
This study investigated financial planning for marriage among young couples in Raub District, Malaysia, focusing on key factors such as financial literacy, attitudes towards money and debt, financial goals, and social influence. Given the increasing levels of indebtedness among young adults and rising divorce rates, this research addresses a crucial theoretical gap in the field of premarital financial planning. Using a quantitative approach, the study employed a structured questionnaire distributed to 48 respondents through an online survey. Data were analysed using Statistical Package for the Social Sciences (SPSS) to perform frequency, descriptive, and reliability analyses. The findings reveal significant patterns and tendencies in financial preparation for marriage, emphasizing the need for proactive financial planning and early financial education. The study highlights that financial planning is essential for achieving financial well-being and satisfaction in marriage. It also underscores the impact of social influences, such as family and peers, on financial behaviours and attitudes. The research contributes valuable insights into the importance of financial literacy and practical financial strategies for young couples, offering recommendations for improving financial planning practices and education in Malaysia.